Trends in postharvest technology, marketing, and distribution of native Australian and South African ornamental plants, cut flowers, and cut foliage - Darras, Anastasios I. (Frontiers in Horticulture, 2025)
The use of flowers in daily human life has a long history and substantiates our appreciation for their delicacy and wide variation in possible shapes and colors. The cultivation and trade of cut flowers and potted ornamental plants have been on the rise in recent years, and these are driven by the growing interest of society for nature and environment. Consequently, it is in the best interest for floriculture specialists and scientists to tap upcoming trends and opportunities for new ornamental crops. Two major areas with global interest in biodiversity are Australia and South Africa. Both serve as global hot spots of endemic flora, and throughout the years, many new species from these continents have been utilized by the floriculture sector. Many ornamental plant species from Australia and South Africa are cultivated in different parts of the world and have established great commercial reputation. In the present review, we highlight the trade potential and the postharvest attributes of some of the most well-known species with international recognition.